Factors Affecting Employee Performance in Public Sector Hospitals in Sudan During the Conflict - Elmagboul, Abdallah; Aini, Qurratul (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2025)
This study examines the factors influencing employee performance in public sector hospitals in Sudan during conflict periods. The research focuses on four key variables: physical health, work environment, work motivation, and job satisfaction. A quantitative cross-sectional survey was conducted using structured questionnaires distributed to healthcare professionals in three public hospitals in Khartoum, Sudan. A random sampling technique was employed to ensure representativeness and 56 responses were analyzed using multiple regression analysis in SPSS. The findings indicate that physical health, work environment, and job satisfaction positively and significantly impact employee performance. However, work motivation has an insignificant effect. These results highlight the necessity for healthcare administrators and policymakers to prioritize improving physical well-being, optimizing workplace conditions, and enhancing job satisfaction to boost employee performance in conflict-affected hospitals. Future research should explore other influencing factors, regional variations, and long-term effects in similar crisis settings.